1980
DOI: 10.1111/j.1744-313x.1980.tb00739.x
|View full text |Cite
|
Sign up to set email alerts
|

HIGH FREQUENCY OF THE PROPERDIN FACTOR Bf F1 AND ITS LINKAGE TO HLA IN FRENCH BASQUES

Abstract: Summary We studied 201 unrelated French Basque individuals for HLA and Bf polymorphisms. The haplotypes of eighty‐seven of them were deduced from family studies. The results show the frequency of the Bf F1 allele (0.1393) which is the highest one currently reported. They confirm the high frequencies of HLA‐Aw19.2 and B18 previously reported in that population and show that a whole haplotype with strong linkage disequilibria, namely Aw19.2, Cw5, B18, Bf F1, DRw3 is frequent. On the other hand, the gene frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In non-European Caucasoids the gene frequency of B f 07 = 0.076 was re ported in Usbeks [Benkmann et al, 1980], in Tunisians BJS0 7 = 0.083 [Davrinche et al, 1981], in Kabyles B f 0 7^ 0.064 [Bouali et al. 1981], and in Saudi Arabs BJS,K7 = 0.059 [Goedde et al, 1979], The gene fre quency of BJS" 7 = 0.151 found in this study is the highest reported frequency of a 'rare' Bf allotype in any population so far reported and exceeds the frequency of another rare Bf allotype, B f = 0.139 found in the Basques [Ohayon et al, 1980].…”
Section: Discussionmentioning
confidence: 68%
“…In non-European Caucasoids the gene frequency of B f 07 = 0.076 was re ported in Usbeks [Benkmann et al, 1980], in Tunisians BJS0 7 = 0.083 [Davrinche et al, 1981], in Kabyles B f 0 7^ 0.064 [Bouali et al. 1981], and in Saudi Arabs BJS,K7 = 0.059 [Goedde et al, 1979], The gene fre quency of BJS" 7 = 0.151 found in this study is the highest reported frequency of a 'rare' Bf allotype in any population so far reported and exceeds the frequency of another rare Bf allotype, B f = 0.139 found in the Basques [Ohayon et al, 1980].…”
Section: Discussionmentioning
confidence: 68%